Implementation of human resource development to improve employee performance - Yuliantari, Putu Devi; Martini, Ida Ayu Oka (International research journal of management, IT and social sciences, 2019)
This study aimed to determine how the implementation of human resource development to improve employee performance on Banyualit Spa ‘n Resort. Human resource development is the people or employee preparation to assume higher responsibilities in the organization or company. Performance is the work result/a process measurement or a person’s achievements regarding tasks assigned to them. The research design used in this study was a descriptive study with a qualitative approach. It was conducted at the Banyualit Spa ‘n Resort located in Lovina, Singaraja Bali. The study results indicated that the Banyualit Spa ‘n Resort has developed human resources well. However, it needs to be improved.